Quantitative Assessment of the Distal Clavicle with Its Clinical Implications in Anatomical Reconstruction of the Coracoclavicular Ligament - Helin Yücedağ Gündoğdu; Hilal Akdemir Aktaş (Düzce Tıp Fakültesi Dergisi)
Aim: Anatomical reconstruction of the coracoclavicular ligament has recently become popular in the treatment of acromioclavicular joint injuries. To perform this procedure correctly, the anatomy of the conoid tubercle and trapezoid line, which are the attachment sites of the coracoclavicular ligament, should be known accurately. Therefore, this study aimed to evaluate the distal clavicle along with morphometry of the conoid tubercle and trapezoid line.Material and Methods: In the present study, 77 human dry clavicles (39 right, 38 left) were examined using a digital caliper and digital thickness gauge. The clavicle length, thickness and width of the distal clavicle, morphometric features of the conoid tubercle, and trapezoid line were examined. Measurements were performed by two researchers independently.Results: The clavicle length was 138.37±10.69 mm. Supero-inferior thickness of the distal clavicle was 9.08±1.69 mm, and the antero-posterior width was 17.70±2.37 mm. Medio-lateral and supero-inferior dimensions of the conoid tubercle were 17.17±3.58 mm and 7.59±1.38 mm, respectively. The distance between the clavicle acromial end and the center of the conoid tubercle was 34.43±5.41 mm. Medio-lateral dimension of trapezoid line was 16.69±2.73 mm, and antero-posterior dimension was 9.61±1.80 mm. The distance between the clavicle acromial end and the center of the trapezoid line was measured as 18.15±2.80 mm.Conclusion: Accordingly, the tunnels for trapezoid and conoid ligaments should be created 18 mm and 34 mm medial from the clavicle acromial end, respectively. The measurements obtained in this study can be used as a guide for coracoclavicular ligament reconstruction.